DIALOG Group Berhad / Muhammad Syahmi Abdullah ... [et al.] - Abdullah, Muhammad Syahmi; Zambari, Muhammad Zafri; Mohd Zani, Mohamad Aliff; Zaidi, Mohamad Akmal Faiz; Affindi, Izz Azri (2019)
The industry that we choose to analyst is petroleum in energy industry. Petroleum is a naturally occurring, yellowish-black liquid found in geological formations beneath the Earth's surface. It is commonly refined into various types of fuels. Components of petroleum are separated using a technique called fractional distillation, separation of a liquid mixture into fractions differing in boiling point by means of distillation, typically using a fractionating column. The energy policy of Malaysia is determined by the Malaysian Government, which address issues of energy production, distribution, and consumption. The Department of Gas Supply acts as the regulator while other players in the energy sector include energy supply and service companies, research and development institutions and consumers. Government- linked company PETRONAS is the major player in Malaysia's energy sector.